Modelling and Simulation of Microturbine for a Distribution System Network with Active Filter - Laili, M. S.; Z. N., Zakaria; A. Z., Abdullah; N. A., Rahman (ENCON 2013, 2013)
Microturbine generation system is one of the distributed generation systems that become an important research interest for many years in the world. The connection of a microturbine generator to a distribution system involves the use of an AC/DC/AC power converter which in turn creates harmonic problems in the distribution system. The necessity of reducing the harmonics injected by the microturbine generation system into the grid is minimized by introducing an active filter. Simulation studies have been carried out in PSCAD/EMTDC and shows that the active filter provides harmonic reduction in the grid current. Furthermore, THD and harmonic spectrum of the grid current with the use of the active filter in the system are studied.